Evaluation of the loop-mediated isothermal amplification assay for Staphylococcus aureus detection: a systematic review and meta-analysis - Li-Jun Long; Min Lin; Yu-Ran Chen; Xin Meng; Ting-Ting Cui; Ya-Ping Li; Xu-Guang Guo (BMC, 2022)
Abstract Background Staphylococcus aureus can cause many diseases and even death. It's important to detect Staphylococcus aureus rapidly and reliably. The accuracy of a novel test named LAMP in detecting Staphylococcus aureus is unclear. Therefore, a systematic review and meta-analysis were conducted to evaluate the accuracy of the LAMP assay for Staphylococcus aureus detection. Methods Four databases were searched for relevant studies. Meta-DiSc 1.4.0 and Stata 12.0 were used for statistical analysis. At the same time, we used QUADAS-2 to assess the studies we included. Two groups of subgroup analysis were done to differentiate the diagnostic effects of various LAMP tests and in cases of different gold standards. Results 11 studies were identified and 19 2 × 2 contingency tables were extracted in our study. The results showed that both pooled sensitivity and specificity of the LAMP assay were 99% (95% CI 99-100). Conclusion The LAMP assay demonstrated high sensitivity and specificity in diagnosing Staphylococcus aureus.